EL GASTO EN INVESTIGACIÓN Y DESARROLLO DE LOS ESTABLECIMIENTOS PÚBLICOS Y PRIVADOS DE ECUADOR, PERIODO 2010-2016, Y LA INCIDENCIA EN SUS INGRESOS - Olaya Maza, Erika Leticia (2018)
The largest number of existing companies in Ecuador, belong to the private sector and have grown more efficiently, compared to the public sector, should indicate that, despite the great effort to grow, income in both sectors has not been sufficient to improve the economy. This income has been affected by inefficient and scarce spending on research and development (R&D). Faced with this problem, the present research has been carried out "The expenditure on research and development of public and private establishments in Ecuador, period 2010-2016, and the incidence on their income". Its general objective was: To determine the expenditure on research and development of public and private establishments in Ecuador, period 2010-2016, through a descriptive-econometric study, in order to establish the incidence on their income. The scope of the research was Ecuador. The scientific method was applied with its expressions or modalities: inductive, deductive, analytical, synthetic and statistical. The main result reached in the investigation was: There is strong and positive correlation between these variables; in public establishments, R&D expenditure is not statistically significant, while in private institutions, it is statistically significant, demonstrating that for each additional dollar in R&D expenditure, the income of establishments would increase by USD 0.169; and, the number of trained workers (researchers) is a primary factor in carrying out R&D activities.